Coastal occupation and foraging during the last glacial maximum and early Holocene at Waterfall Bluff, eastern Pondoland, South Africa. Issue 1 (September 2020) - Fisher, Erich C.; Cawthra, Hayley C.; Esteban, Irene; Jerardino, Antonieta; Neumann, Frank H.; Oertle, Annette; Pargeter, Justin; Saktura, Rosaria B.; Szabó, Katherine; Winkler, Stephan; Zohar, Irit
Abstract: Waterfall Bluff is a rock shelter in eastern Pondoland, South Africa, adjacent to a narrow continental shelf that limited coastline movements across glacial/interglacial cycles. The archaeological deposits are characterized by well-preserved stratigraphy, faunal, and botanical remains alongside abundant stone artifacts and other materials. A comprehensive dating protocol consisting of 5 optically stimulated luminescence ages and 51 accelerator mass spectrometry 14 C ages shows that the record of hunter-gatherer occupations at Waterfall Bluff persisted from the late Pleistocene to the Holocene, spanning the last glacial maximum and the transition from the Pleistocene to the Holocene. Here, we provide detailed descriptions about the sedimentary sequence, chronology, and characteristics of the archaeological deposits at Waterfall Bluff. Remains of marine mollusks and marine fish also show, for the first time, that coastal foraging was a component of some hunter-gatherer groups' subsistence practices during glacial phases in the late Pleistocene. The presence of marine fish and shellfish further demonstrates that hunter-gatherers selectively targeted coastal resources from intertidal and estuarine habitats. Our results therefore underscore the idea that Pondoland's coastline remained a stable and predictable point on the landscape over the last glacial/interglacial transition being well positioned for hunter-gatherers to access resources from the nearby coastline, narrow continental shelf, and inland areas.